Development of an educational interventionist project with truck drives at the BR-040 highway - Arreguy-Sena, Cristina; Hallack, Kalil Abrahão; Rodrigues, Patrícia Rios; Mielo , Marcos; Sena, Kanthya Arreguy de (Brazilian Journal of Sexually Transmitted Diseases, 1999)
Introduction: the Universidade Federal de Juiz de Fora, Minas women in Brazil Gerais Multiprofession Center on Aids is compounded of professors who develop campaigns on prevention and control of sexually transmissible diseases/HIV / Aids in Juiz de Fora, and surroundings. Analyzing the local ne-eds, we observed an increase in the number of tru-ck drivers travelling on BR 040 (Federal road that connects the States of Rio de Janeiro, São Paulo and Minas Gerais) and the necessity to develop an educational campaign on the prevention of Aids and · other sexually transmissible diseases, aiming tru-ck drivers. Study objective: describe activities de-veloped aiming truck drivers who travel on BR040. Method and discussion: to deal with truck drives requires, at first place, to know their profile in ar-der to allow proper communication with them. Edu-cational activities are developed by approximately 50 people among students and professors from di-fferent Colleges and Institutes of the Federal Uni-versity of CONCER with support from the National and State Coordinations ofVenereal Diseases/ Aids. Voluntary students and teachers are divided into eight to ten group of four members each, on both sides of BR 040, The traffic is stopped by the poli-cemen and members of CONCER. Individual assis-tance is given in order to show drives how to put on a condom properly and afterwards there is the dis-tribu tion of folders and free preservatives, Then all the data collected is registered. This dynamic lasts for four hours and provides contact with 200 to 600 truck drivers per day. Results: the feed-back provi-ded by truck drives in one year on activities on BR 040 shows the social importance ofthe UFJF in pro-viding information on the prevention of sexually transmissible diseases/ Aids to this group. Besides that the intercourse between teachers and students has allowed the change of experiences between di-fferent professional areas.